UPAYA MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR SISWA MELALUI MODEL GROUP INVESTIGATION PADA MATA PELAJARAN MENGOPERASIKAN PERALATAN KANTOR DI SMK NEGERI 1 SUKOHARJO TAHUN AJARAN 2015/2016 - Mujiono, Mujiono; Joyoatmojo, Soetarno; Santoso Th, Djoko (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2017)
The purpose of this study is to enhance the activity and student achievement in the subjects operate office equipment Office class XI student of SMK Negeri 1 Sukoharjo.This research used the Classroom Action Research (CAR). The study was conducted in two cycles, with each cycle consisting of planning, action, observation and reflection. The subjects were students of class XI Departement Office of State Vocational High School 1 Sukoharjototaling 32 students. Source of data derived from students, teachers, and documents. Data collection techniques are observation, testing, documentation and interviews. Techniques for the validity of the data used triangulation of data sources and triangulation methods. The data analysis technique used is descriptive analysis techniques , qualitative analysis techniques and comparative description.The results of research shows that through the application of cooperative learning model with type Group Investigation (GI) can improve activeness and learning achievement Manage office equipment at Grade XI Departement Office State Vocational High School 1 Sukoharjo In Academic Year 2015/2016. The increase occurred in the first cycle and the second cycle. Before application of cooperative learning model with type Group Investigation (GI) grade average score is 73 with the percentage of completeness 34.8%. In the first cycle class average value increased to 77.12 with the percentage of completeness 78.13% and the second cycle the average value increased to 80 grade with a percentage of completeness 84.83%. The conclusions of this research is the application of cooperative learning model type Group Investigation (GI) can improve learning achievement Goods Administration subject matter in Grade XI Marketing of State Vocational High School 1 Sukoharjo.